A systematic approach to the management of microspherophakia - Prasanna Venkataraman; Aravind Haripriya; Neethu Mohan; Anand Rajendran (Indian Journal of Ophthalmology, 2022)
Microspherophakia is a rare developmental abnormality of the crystalline lens with a myriad of ocular and systemic associations. Glaucoma is a serious complication associated with this disorder. Early identification of the disease, timely visual rehabilitation, and appropriate management of the lens and glaucoma can help us prevent blindness from this condition. Multidisciplinary care with lifelong follow-up is recommended, as this typically affects the younger population. Current treatment protocols for this condition are mainly based on case reports and retrospective studies with shorter follow-up. Due to the rarity of this disease, designing a large randomized controlled trial to identify the merits and demerits of each management strategy is challenging. With cataract, glaucoma, and vitreoretinal specialists, each having their preferred way of managing microspherophakic lenses, we decided to do a comprehensive review of the existing literature to devise an integrated approach toward effective management of these patients. This review will collate all evidence and provide a very practical decision-making tree for its management.